Issues of awards given as a part of social arbitration in a collective dispute. De lege lata and de lege ferenda remarks - Jarota, Maciej (Review of European and Comparative Law, 2022)
Social arbitration as the third method of resolution of collective disputes can be used to resolve a dispute in an amicable manner. Thanks to this method, parties to the collective dispute can end their conflict thanks to the arbitration award with no need to go on strike. The author analyses the legal nature of arbitration awards and presents consequences of the related labour law legislation. The conclusion is as follows: current legal regulations are in need of change, especially when it comes to the execution, amendment and supplementation of an award issues as a part of social arbitration with the involvement of trade unions, employers or their organisations.